Kristeva, Ethics and Intellectual Practice - Gambaudo, Sylvie (Text Matters: A Journal of Literature, Theory and Culture, 2014)
The aim of this article is to revisit the work of the French philosopher Julia Kristeva and ask what place we might give her conceptual framework today. I will focus on one key aspect of Kristeva’s work, sexual difference, as that which ties most, if not all, aspects of Kristeva’s work. I am hoping to present a concise, yet wide-ranging view on Kristeva’s critical contribution to the fields of politics and ethics. My objective will be threefold. First, I will present the main lines of Kristeva’s theory on sexual difference; this presentation will also outline her political critique of equality and diversity in the domains of gender and sexuality. Kristeva believes that contemporary politics invested in suppressing inequality through the promotion of diversity will in the long term not only prove unsuccessful, but also create more exclusion. Secondly, I will point out the main objections raised against her theories and show how her critics come to their conclusions. Objectors to Kristeva’s sexual difference theory are mostly concerned with the manner in which she associates marginality and unintelligibility. They see little value in her theory, because, on the one hand, it relegates marginal groups to a world beyond social viability, and, on the other, because it effectively disables advancements in equality politics. Finally, I hope to provide the reader with a useful counter-critique to Kristeva’s detractors that will show why their views are partly founded on a misreading of her ethical (Freudian) framework and a desire to translate her work into a more pragmatic and user-friendly tool. I will argue that Kristeva’s work is best apprehended as a variant of psychoanalytic ethics and that to engage with its rhetoric is to capture the full weight of Kristeva’s contribution to politics and intellectual engagement.